ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGISIAN REKAM MEDIS DI RUMAH SAKIT GIGI DAN MULUT PENDIDIKAN UMY - Khasib Mabrur Ridho; Elsye Maria Rosa; Endang Suparniati (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
Background: RSGMP UMY been utilizing computer-based information systems and manually medical records. Problems often arise in filing medical records are incomplete filling process. The purpose of this study to find out the problems in filling medical records, and analyzes the factors that influence adherence charging medical records in RSGMP UMY. Method: using quantitative and qualitative methods. Subjects in research is coass and physician mentors in RSGMP UMY. Research object is files medical records in 2012. Quantitative data using descriptive statistics, qualitative data using a coding interview. Results: The complete medical records of 236 (64.84%), and incomplete medical records of 128 (35.16%). Incomplete completeness aspect is the identity of the patients (3.85%), the date and time (1.65%), the name and signature of the doctor (23.35%), and correction of errors (16.21%). Medical record is incomplete due to factors selecting lecturers, lack of faculty, number of patients, limited time, knowledge, and attitudes operator. Conclusion: Factors affecting compliance to medical records in RSGM-P UMY is knowledge, limited time, operator attitude, sum of patient, and motivation.